RELIGIOUS MODERATION AS A FOUNDATIONAL UNDERSTANDING IN STRENGTHENING SOCIAL HARMONY IN SIMPANG EMPAT VILLAGE, SIMPANG EMPAT DISTRICT, ASAHAN REGENCY - Muhammad Daffa Juanda; Annaisaburi (SOSIOEDUKASI, 2026)
This research is motivated by the importance of religious moderation in creating a harmonious and harmonious community life amidst religious diversity. Simpang Empat Village once experienced a major interfaith conflict related to the rejection of the construction of a house of worship, but the conflict did not last long and was resolved through deliberation. This condition indicates a learning process towards a more peaceful and tolerant community life. This study aims to determine the community's understanding of religious moderation and its role in improving community harmony. This study uses a qualitative approach with a phenomenological research type, using primary data in the form of interviews with local religious leaders and secondary data from books, journals, and the internet. The results show that religious moderation can be a foundation for building a harmonious society through tolerance, mutual respect, and a forum for interfaith cooperation such as BKUK, which has been successfully implemented and is the main goal in maintaining community harmony in the village. The conclusion of this study is that local religious leaders play an important role in educating religious moderation and building a harmonious society. Therefore, there needs to be cooperation between religious leaders and the community to spread religious moderation because religious moderation can help reduce conflict and increase tolerance between communities and create a peaceful and harmonious community life in Simpang Empat village.